The interpretative arguments from legislator's intention: troublesome profiles - Poggi, Francesca; Asta, Francesca (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
This essay aims to examine the interpretative argument of the legislator’s intention. We will distinguish six variants of this argument: three variants referring to historical legislators and three variants referring to an ideal, rational legislator. For each of them, we will give examples and explain the values that justify them. Then, we will present the theoretical criticisms directed against each variant: in support of these criticisms, we will alsopresent the results of a recent empirical research carried out in the Italian legalsystem. We will argue that the theoretical criticisms are justified. The variantsreferring to the intention of historical legislators raise conceptual, ontologicaland epistemic problems and, in fact, are rarely employed (at least in Italian caselaw). The variants referring to the ideal legislator, on the other hand, open uproom for judicial discretion.
Keywords: legislative intention; legislator’s purpose; ratio legis; legal interpretation